Teaching reading, writing and speaking practices in the Bachelor of Social Work: preliminary results of an action-research (Teresa Vigetti: Revista de Trabajo Social, 2025)
This article presents some results of an action-research carried out within the framework of the “Licenciatura en Trabajo Social” de la Facultad de Ciencias Jurídicas y Sociales, of the Universidad Nacional del Litoral (Santa Fe, Argentina), during the period 2023-2024. This research made it possible to build, test, systematize and analyze some emerging didactic strategies that can be deployed in classrooms to contribute to the improvement of teaching and that are an alternative to the master class as they make it possible to accompany students during the learning of reading, writing and oral practices, within the framework of a specific discipline: Social Work.
Keywords: academic literacy; teaching; university; social work